Concurrent Methane Production and Oxidation in Surface Sediment from Aarhus Bay, Denmark - Xiao, Ke-Qing; Beulig, Felix; Kjeldsen, Kasper U.; Jørgensen, Bo B.; Risgaard-Petersen, Nils (Frontiers in Microbiology, 2017)
Marine surface sediments, which are replete with sulfate, are typically considered to be devoid of endogenous methanogenesis. Yet, methanogenic archaea are present in those sediments, suggesting a potential for methanogenesis. We used an isotope dilution method based on sediment bag incubation and spiking with 13C-CH4 to quantify CH4 turnover rates in sediment from Aarhus Bay, Denmark. In two independent experiments, highest CH4 production and oxidation rates (>200 pmol cm-3 d-1 ) were found in the top 0-2 cm, below which rates dropped below 100 pmol cm-3 d-1 in all other segments. This drop in overall methane turnover with depth was accompanied by decreasing rates of organic matter mineralization with depth. Molecular analyses based on quantitative PCR and MiSeq sequencing of archaeal 16S rRNA genes showed that the abundance of methanogenic archaea also peaked in the top 0-2 cm segment. Based on the community profiling, hydrogentrophic and methylotrophic methanogens dominated among the methanogenic archaea in general, suggesting that methanogenesis in surface sediment could be driven by both CO2 reduction and fermentation of methylated compounds. Our results show the existence of high methanogenic activity and a dynamic recycling of CH4 at low concentration in sulfate-rich marine surface sediment. Considering the common environmental conditions found in other coastal systems, we speculate that such a cryptic methane cycling can be ubiquitous.